Fungal families of the world - Cannon, P. F. (Paul F.); Kirk, P. M. (Paul M.) (CABI, 2007)
This book portrays the immense diversity of the Kingdom Fungi. Detailed information is provided on all 536 currently recognized families, describing their morphology, ecology, phylogeny, distribution and economic significance. Presented in a new, larger format, entries are illustrated in full colour, with nearly 900 example species depicted, and include carefully selected references to aid further reading.